Application of a 245 metric ton Dual-Use Active TMD System. (2017) - Meinhardt, Christian; Nikitas, Nikolaos; Demetriou, Demetris
Abstract: The slender design of a 245 m tall tower structure requires additional structural damping to reduce vortex shedding induced vibrations. Wind tunnel tests indicate that wind speeds can produce critical accelerations at the observation deck on the tower's top level. The resulting displacements not only raise concern regarding the fatigue capacity at the concrete core of the tower, but would also lead to the discomfort of its visitors. To mitigate critical displacements, a state of the art passive Tuned Mass Damper (TMD) system was chosen to be implemented. The primary use of the tower is not only to give visitors access to its observation deck but to also serve as a test facility for equipment susceptible to building sway. To test the equipment under real life conditions the TMD system is required to be either in passive or in active mode, where in the latter it could excite the tower in its fundamental mode of vibration and cause a significant, yet controlled, building sway in any direction. To satisfy these requirements a novel dual purpose active/passive TMD system was developed. This hybrid TMD is capable of even suppressing the occurring vibrations in one direction while, with the aid of active control, synchronously exciting the tower's perpendicular direction. The following paper reports on the design approach of the passive system and describes the control strategy when switched into excitation mode. The initial optimization approach will be presented as well as the in-situ results of vibration tests during a monitoring campaign on the tower. In addition, the safety concept to avoid excessive displacements of the tower will be presented.